Building a collaboration to improve surgical research through EORTC/ESSO 1409-CLIMB study: A prospective liver metastasis database with an integrated quality assurance program. Issue 10 (October 2019) - Caballero, Carmela; Burock, Susen; Carrion-Alvarez, Lucia; Nilsson, Henrik; Ruers, Theo; Senellart, Perrine; Rivoire, Michel; Stattner, Stefan; Primavesi, Florian; Troisi, Roberto; Gruenberger, Thomas; Heil, Jan; et al.
Abstract: The challenges of conducting surgical oncology trials have resulted to low quantity and poor quality research [1, 2]. Considering the definitive role of surgery to offer cure, immediate response to improve surgical research is needed [3]. The European Organization for Research and Treatment of Cancer (EORTC) and the European Society of Surgical Oncology (ESSO) share the vision to achieve excellent surgical research and care for cancer patients. Building on their complimentary expertise, they embarked on a pilot project to map out challenges and initiate a sustainable collaboration to advance cancer surgery research in Europe. This pilot project is EORTC-ESSO 1409 GITCG/ ESSO-01: A Prospective Colorectal Liver Metastasis Database with an Integrated Quality Assurance Program (CLIMB). This article will describe the challenges, milestones and vision of both organizations in setting up this collaboration.